Meta-Model Based Scaling Laws of a Two-Winding Transformer - Tahir, Ahmed (Libyan Journal for Engineering Research, 2017)
Recently, there has been growing interest in system-based global optimization techniques for the design of small systems such as micro-grids. To reduce the search space of the global optimization technique, a meta-model based scaling law was introduced. In this paper, a scaling technique was derived in which a transformer mass and power loss were expressed in terms of rated power, specified current density, and frequency. Curve-fitting techniques were used to derive a meta-model for the scaled mass and power loss. To achieve more generality, the meta-model was also defined as a function of frequency.